Impact of endoscopic ultrasound-guided fine-needle aspiration and multidisciplinary approach in the management of abdominal or mediastinal mass. Issue 9 (September 2015) - Del Vecchio Blanco, Giovanna; Coppola, Manuela; Mannisi, Elena; Bevivino, Gerolamo; Formica, Vincenzo; Portarena, Ilaria; Romeo, Samanta; Sileri, Pierpaolo; Roselli, Mario; Pallone, Francesco; Paoluzi, Omero Alessandro
<x xml:space="preserve">Abstract</x> Background Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) is a useful tool for the diagnosis of suspected abdominal or mediastinal neoplastic lesions. Aim To evaluate the impact of EUS-FNA and multidisciplinary approach on the diagnostic work-up and therapeutic management of patients with abdominal or mediastinal neoplastic lesions. Patients and methods One hundred and twenty patients (69 men, median age 65 years) with a suspected abdominal or mediastinal neoplastic mass at computed tomography or MRI underwent EUS-FNA. All EUS-FNA findings and clinical data were evaluated by a multidisciplinary team (oncologists, surgeons, and gastroenterologists). EUS-FNA findings were compared with the final diagnosis made by histological evaluation of the surgical specimen or clinical outcome at follow-up. Results A correct diagnosis was obtained by EUS-FNA in 96/120 patients (80%), indicating benignancy of the lesion in 21 (18%) cases and confirming malignancy in 75 (62%). On the basis of EUS-FNA findings, chemotherapy was tailored in 57/75 (76%) patients with malignancy whereas the surgical strategy was changed in 21/120 (18%) of patients. Overall, the diagnostic accuracy of EUS-FNA was 85%. A multidisciplinary team approach enabled a correct diagnosis in patients in whom EUS-FNA was nondiagnostic and to identify five cases with false-negative EUS-FNA findings. Conclusion EUS-FNA has a relevant impact on the management of suspected abdominal or mediastinal neoplastic lesions. A multidisciplinary team approach enables to overcome the EUS-FNA methodological limitations. The combination of EUS-FNA and multidisciplinary team approach could help to diagnose and tailor therapeutic options in such patients.